Technological Change and Energy Demand in Europe - Kurt Kratena; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2012)
The aim of this paper is the econometric analysis of embodied and induced technological change that reduces energy input and CO2 emissions in production. For this purpose, a model of unit costs and factor demand for 35 industries in 23 EU countries has been set up, based on the World Input-Output Database (WIOD). The deterministic trend usually applied for describing the factor bias for energy is replaced by a mixed term of energy efficiency of physical production capacity and a trend in three energy intensive industries. This new variable for energy saving technological change is linked to the vintage structure of installed capital. By this link technological change becomes induced, if capital and energy are substitutes. If energy and capital are complements, this technological change can only be enforced by measures that accelerate the path of renovating the capital stock. Within the three energy intensive industries we identify one, where induced technological change is energy saving, but energy and capital are complements (pulp and paper), one where energy and capital are very weak substitutes, but technological change is energy using (non-metallic minerals) and one, where energy and capital are substitutes and technological change is energy saving (basic metals). Only in this latter case, price induced technological change can contribute significantly to fossil energy and emission reduction.
Keywords: 330; embodied and induced technological change; vintage models; emission mitigation policies; Energiekonsum; Umweltbelastung; Industrieforschung; Energieeinsparung; EU-Staaten